Isolation of Cellulolytic Bacterium Staphylococcus sp. JC20 from the Intestine of Octopus (Octopus sp.) for Fish Probiotic Candidate - Indah Istiqomah; Alim Isnansetyo; Imelda Novita Atitus; Ahmad Fauzi Rohman (Universitas Gadjah Mada, 2019)
Aim of this study was to isolate, characterize, and identify cellulolytic bacteria from the digestive tract of marine vertebrates and invertebrates as a candidate of fish probiotics. The bacteria were isolated from the digestive tract and grown on a cellulose agar plate. The bacteria were screened based on the cellulolytic activity, acid resistance, antagonist activity against fish pathogens, antibiotics sensitivity, ability to live in fish digestive tract and non-pathogenic test. Selected bacterium was identified molecularly, based on the 16S rDNA gene sequences, and phenotipically. A total of 14 bacteria demonstrated celulolitic index of 1.1-1.8. The bacteria with cellulolytic index of > 1.6 were screened by the selection criteria, resulted a selected strain, JC20 isolate which was isolated from the digestive tract of octopus (Octopus sp.). The selected bacterium was sensitive to antibiotics, resists to acidic environment, able to live in the fish digestive tract, and non-pathogen. Thus, the bacterium was potential for further characterization as fish probiotics candidate. Molecular and phenotypic identification revealed that JC20 isolate was Staphylococcus sp.